A genotype-first approach identifies an intellectual disability-overweight syndrome caused by PHIP haploinsufficiency. (January 2018) - Jansen, Sandra; Hoischen, Alexander; Coe, Bradley; Carvill, Gemma; Esch, Hilde; Bosch, Daniëlle; Andersen, Ulla; Baker, Carl; Bauters, Marijke; Bernier, Raphael; Bon, Bregje; Claahsen-van der Grinten, Hedi; et al.
Abstract Genotype-first combined with reverse phenotyping has shown to be a powerful tool in human genetics, especially in the era of next generation sequencing. This combines the identification of individuals with mutations in the same gene and linking these to consistent (endo)phenotypes to establish disease causality. We have performed a MIP (molecular inversion probe)-based targeted re-sequencing study in 3, 275 individuals with intellectual disability (ID) to facilitate a genotype-first approach for 24 genes previously implicated in ID. Combining our data with data from a publicly available database, we confirmed 11 of these 24 genes to be relevant for ID. Amongst these, PHIP was shown to have an enrichment of disruptive mutations in the individuals with ID (5 out of 3, 275). Through international collaboration, we identified a total of 23 individuals withPHIP mutations and elucidated the associated phenotype. Remarkably, all 23 individuals had developmental delay/ID and the majority were overweight or obese. Other features comprised behavioral problems (hyperactivity, aggression, features of autism and/or mood disorder) and dysmorphisms (full eyebrows and/or synophrys, upturned nose, large ears and tapering fingers). Interestingly, PHIP encodes two protein-isoforms, PHIP/DCAF14 and NDRP, each involved in neurodevelopmental processes, including E3 ubiquitination and neuronal differentiation. Detailed genotype-phenotype analysis points towards haploinsufficiency ofPHIP/DCAF14, and notNDRP, as the underlying cause of the phenotype. Thus, we demonstrated the use of large scale re-sequencing by MIPs, followed by reverse phenotyping, as a constructive approach to verify candidate disease genes and identify novel syndromes, highlighted byPHIP haploinsufficiency causing an ID-overweight syndrome.